Respuesta :
━━━━━━━☆☆━━━━━━━
▹ Answer
Answer = b. 13/5
▹ Step-by-Step Explanation
|4 - 5| ÷ 9 × 3³ - 2/5
|-1| ÷ 9 × 3³ - 2/5
1 ÷ 9 × 3³ - 2/5
1/9 × 3³ - 2/5
1/3² × 3³ - 2/5
3 - 2/5
Answer = 13/5
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer:
[tex] \boxed{\sf b. \ \frac{13}{5}} [/tex]
Step-by-step explanation:
[tex] \sf Simplify \: the \: following: \\ \sf \implies \frac{ |4 - 5| }{9} \times {3}^{3} - \frac{2}{5} \\ \\ \sf 4 - 5 = - 1 : \\ \sf \implies \frac{ | - 1| }{9} \times {3}^{3} - \frac{2}{5} \\ \\ \sf Since \: - 1 \: is \: a \: negative \: constant, \: |-1| = 1: \\ \sf \implies \frac{1}{9} \times {3}^{3} - \frac{2}{5} \\ \\ \sf {3}^{3} = 3 \times {3}^{2} : \\ \sf \implies \frac{ \boxed{ \sf 3 \times {3}^{2}} }{9} - \frac{2}{5} \\ \\ \sf {3}^{2} = 9 : \\ \sf \implies \frac{3 \times 9}{9} - \frac{2}{5} \\ \\ \sf \frac{9}{9} = 1 : \\ \sf \implies 3 - \frac{2}{5} [/tex]
[tex] \sf Put \: 3 - \frac{2}{5} \: over \: the \: common \: denominator \: 5 : \\ \sf \implies 3 \times \frac{5}{5} - \frac{2}{5} \\ \\ \sf \implies \frac{3 \times 5}{5} - \frac{2}{5} \\ \\ \sf 3 \times 5 = 15 : \\ \sf \implies \frac{ \boxed{ \sf 15}}{5} - \frac{2}{5} \\ \\ \sf \implies \frac{15 - 2}{5} \\ \\ \sf 15 - 2 = 13 : \\ \sf \implies \frac{13}{5} [/tex]